Экстракция данных для теплоэнергетической интеграции процесса четыреххлористого титана методом ректификации - Сивак, В. В.; Ульев, Леонид Михайлович; Сулима, А. М. (НТУ "ХПИ", 2012)
The flowsheet for new titanium tetrachloride cleaning process with rectification method with simultaneous vanadium oxitrichloride production is presented in this paper. Flowsheet studding and literature analysis allow to define the technological streams for process heat energy integration. The thermal physic and technological parameters were defined for streams. This allows us to create the streams table which is the numerical image of recuperation system and the base for process integration
Keywords: металлургическая промышленность; титановая губка; металлический ванадий; примеси